A competitive coordination-based immobilization-free electrochemical biosensor for highly sensitive detection of arsenic(v) using a CeO2–DNA nanoprobe. Issue 39 (13th April 2020) - Yang, Limin; An, Bin; Yin, Xuehan; Li, Feng
Abstract : A competitive coordination-based immobilization-free electrochemical biosensor was developed for highly sensitive detection of arsenic(v ) using a CeO2 –DNA nanoprobe. Abstract : We developed a competitive coordination-based immobilization-free electrochemical biosensor for highly sensitive and selective detection of arsenic(v ) using a CeO2 –DNA nanoprobe, which effectively circumvented complicated modification procedures and successfully achieved arsenic(v ) determination in natural water samples.